Rainwater Harvesting Systems That Reduce Water Consumption With Optimal Locations of Solar Concentration Power Plants - Murillo-Alvarado, Pascual Eduardo; Cárdenas Gil, Marco Antonio (Frontiers in Energy Research, 2022)
At present, the increase in population has caused an increase in the demand for electrical energy, which creates saturation in the national electrical system. In addition to this, the main source of energy for the generation of electricity is fossil fuels, which causes environmental pollution problems due to the increase in the concentration of greenhouse gases. To counteract the negative environmental impact, new energy sources that are friendlier to the environment have been sought, such as solar energy through power generation plants using solar concentrators. In this sense, this research proposes a mathematical optimization model to determine the feasibility of installing electric power generation plants through solar concentrators, to satisfy the energy demand in cities with the highest demand for electric power in the state of Michoacán. The proposed model considers the availability of water resources, the demand for energy, the costs involved for the installation of power generation plants, and the sizing of water collection systems to reduce the consumption of fresh water that is extracted from natural sources. It is a linear integer mixed programming model, where two scenarios are analyzed, considering variation in the operating time of the thermal storage system and the incorporation of the rainwater harvesting system to reduce freshwater consumption. The results show that 237,600 MW can be produced by installing three of the six power generation plants considered and considering a 19 h operation with thermal storage, generating a profit from the sales of the energy produced of 6,326,700 USD/year. Likewise, with the sizing of the rainwater harvesting system, it is possible to collect 1,678 m3 for the operation of the three determined power generation plants.